PENGARUH LATIHAN LINEOUT EVASION TERHADAP KELINCAHAN PADA TIM SEPAK BOLA SSB UNIVERSITAS RIAU - Juita, Ardiah Juita; ', Doraemon; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem in this research is whether there is a influence of Lineout Evasion Drill to Agility. The goal is to find out how big the influence the drill to agility at foot ball team of SSB Riau University. The technique of sampling performed is used total sampling of 18 students of foot ball team of SSB Riau Uniersity. This research is experimental research. The research conducted on students of foot ball team of SSB Riau Uniersity. Data were obtained and collected through the pretest and posttest before and after does exercise. Data was analyzed with used t-test Then, the data are tested using test normality and t- test of the significance level is Î± = 0.05. the Test normality of pretest is L0maks < 0,131 < Ltabel =0,200 and normalitty of post test is L0maks = 0,123 < Ltabel = 0,200 in other words at a confidence level 95% data is normal. Result of t- test analyzes pretest and post test showed =12,09 with =1,740 at significan level a= 0,05. So that the hypotesis is accepted. It can be concluded that there is a signifikan effect of Lineout Evasin Drill to Agility and concluded the results showed: there is a significant influence of Lineout Evasin Drill to Agility at foot ball team of SSB Riau University. So that Ho rejected and H1 accepted.Key word: influence, lineout evasion, agility,